Carbapenem Derivatives as Potential Inhibitors of Various β-Lactamases, Including Class B Metallo-β-Lactamases - Nagano, Rie (American Society for Microbiology, 1999)
A variety of 1β-methylcarbapenem derivatives were screened to identify inhibitors of IMP-1 metallo-β-lactamase, a class B β-lactamase, in an automated microassay system using nitrocefin as a substrate. The structure–inhibitory-activity relationship study revealed that three types of 1β-methylcarbapenems having benzothienylthio, dithiocarbamate, or pyrrolidinylthio moieties at the C-2 position showed good inhibitory activity. Among the compounds screened, J-110,441, having a benzothienylthio moiety at the C-2 position of 1β-methylcarbapenem, was the most potent inhibitor of class B metallo-β-lactamases with K(i) values of 0.0037, 0.23, 1.00, and 0.83 μM for IMP-1 encoded by the bla(IMP) gene, CcrA from Bacteroides fragilis, L1 from Stenotrophomonas maltophilia, and type II from Bacillus cereus, respectively. In a further characterization study, J-110,441 also showed inhibitory activity against TEM-type class A serine β-lactamase and chromosomal class C serine β-lactamase from Enterobacter cloacae with K(i) values of 2.54 and 0.037 μM, respectively. Combining imipenem or ceftazidime with J-110,441 had a synergistic effect on the antimicrobial activity against β-lactamase-producing bacteria. Against the isolates of IMP-1-producing Serratia marcescens, the MICs of imipenem decreased to levels ranging from 1/64 to 1/4 in the presence of one-fourth of the MIC of J-110,441. Against E. cloacae producing high levels of class C β-lactamase, the MIC of ceftazidime decreased from 64 to 4 μg/ml in the presence of 4 μg of J-110,441 per ml. This is the first report to describe a new class of inhibitor of class B and class C β-lactamases including transferable IMP-1 metallo-β-lactamases.